Efek Pemberian Beberapa Dosis Mirkroorganisme Selulolitik (MOS) dan Pupuk Anorganik pada Tanaman Kelapa Sawit (Elaeis guineensis Jacq) di TBM-III - Suhandi Maulana S; Gusmawartati '; Sampoerno ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The research has been conducted to knowing Mikroorganisme Selulolitic Doses (MOS) and Inorganic Fertilizers in Immature Plants Oil Palm (elaeis guineensis Jacq) – III. The research was conducted at the PT. Tunggal Perkasa Plantation Air Molek, sub-district Pasir Penyu, district Indragiri Hulu-Riau  from March to June 2013. The experiment using random design group (RAK) with two factor. The first factor is doses of mikroorganisme selulolitic consists of four levels (0;10;20 and 30 mL/plants) and doses of inorganic fertilizers consists of two levels ((½ and ¾ recommendations doses /plants). The data is analyzed by using the Analysis of Variance (ANOVA) and Duncan’s New Multiple Range Test (DNMRT) at level 5%. The results showed that the effect of mikroorganisme selulolitic (MOS) influential real to long of rachis and the leaves. Effect of 30 mL microorganism selulolitic (MOS)  and ½ doses inorganic fertilizers can increase around of trunk, long of rachis and long of leaves. Effect of 10 mL microorganism selulolitic (MOS) and ½ doses inorganic fertilizers can increase add child leaves , long of petiole and width of child leaves. Keywords : Mikroorganisme Selulolitic (MOS), Inorganic Fertilizers, Oil Palm